2013
DOI: 10.1093/toxsci/kft020
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Phosphate Esters Within a Major PentaBDE Replacement Product Induce Cardiotoxicity in Developing Zebrafish Embryos: Potential Role of the Aryl Hydrocarbon Receptor

Abstract: Firemaster 550 (FM550) is an additive flame retardant formulation of brominated and aryl phosphate ester (APE) components introduced as a major replacement product for the commercial polybrominated diphenyl ether mixture (known as PentaBDE) used primarily in polyurethane foam. However, little is known about the potential effects of FM550-based ingredients during early vertebrate development. Therefore, we first screened the developmental toxicity of each FM550 component using zebrafish as an animal model. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(130 citation statements)
references
References 41 publications
7
123
0
Order By: Relevance
“…Considering both results of heart rate and SV-BA distance, 0-48 hpf is the most vulnerable developmental window in which cardiomyogenesis and cardiac function can be affected by TPhP and CDP, which is similar to the results found in TDCPP and ITP studies (McGee et al, 2012(McGee et al, , 2013.…”
Section: -48 Hpf Is the Vulnerable Window Of Zebrafish Cardiogenesissupporting
confidence: 83%
See 3 more Smart Citations
“…Considering both results of heart rate and SV-BA distance, 0-48 hpf is the most vulnerable developmental window in which cardiomyogenesis and cardiac function can be affected by TPhP and CDP, which is similar to the results found in TDCPP and ITP studies (McGee et al, 2012(McGee et al, , 2013.…”
Section: -48 Hpf Is the Vulnerable Window Of Zebrafish Cardiogenesissupporting
confidence: 83%
“…McGee et al (2013) suggested that the similar cardiotoxicity phenotype induced by TPhP and ITP in zebrafish embryos were respectively through AHR independent and AHR1-dependent pathways. In order to understand the internal reason for TPhP and CDP induced cardiotoxicity, we further explored the changes in expressions of key transcriptional regulators in cardiac development.…”
Section: Tphp and Cdp Disturbed Expressions Of Key Transcriptional Rementioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies have demonstrated that several OP esters cause developmental toxicity and endocrine disruption in vivo and in vitro (Crump et al, 2012;Dishaw et al, 2012;Farhat et al, 2013;Fu et al, 2013;Liu et al, 2012bLiu et al, , 2013McGee et al, 2012McGee et al, , 2013Wang et al, 2013). For example, exposure of zebrafish embryos to tris(1,3-dichloro-2-propyl) phosphate (TDCPP) disrupted embryogenesis and caused larval malformation, with median lethal concentrations (LC 50 ) ranging from 3.7 to 7.0 mg/L (Fu et al, 2013;Liu et al, 2013;McGee et al, 2012;Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%